Transfusion-Transmissible Infections among Voluntary Blood Donors at Wolaita Sodo University Teaching Referral Hospital, South Ethiopia - Fithamlak Solomon Bisetegen; Fanuel Belayneh Bekele; Temesgen Anjulo Ageru; Fiseha Wadilo Wada (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Transfusion-transmissible infections, human immunodeficiency virus, hepatitis B virus, hepatitis C virus, and syphilis are among the greatest threats to blood safety and pose a serious public health problem. Objective. To determine the magnitude of blood borne infections among blood donors at Wolaita Sodo University Teaching Referral Hospital. Methods and Materials. A cross-sectional study was conducted from 10/11/2015 up to 10/12/2015. 390 donors were consecutively included and data on donor’s age, sex, blood type, and serum screening results were obtained by structured questionnaire and laboratory investigation. The collected data were entered into Epi Data version 1.4 and then exported to SPSS version 20.0 for analysis. Result. The seroprevalence of blood borne pathogens is 29.5% of which HCV, HBV, HIV, and syphilis account for 8.5%, 9.5%, 6.4%, and 7.5%, respectively. Multiple infections were observed among 2.8% of the infected individuals. In addition, age ≥ 30 has a significant association with HCV. Conclusion. Significantly higher prevalence of transfusion-transmissible infections was identified from blood donors and they remain to be the greatest threat to blood safety, so comprehensive screening of donors’ blood for HIV, HBV, HCV, and syphilis using standard methods is highly recommended to ensure the safety of blood recipient.